The Cruciality of the Objectified Body in Samiya At’ut’s That Summer Holiday - Rommel Utungga Pasopati; Laila Nabilahtuzzahro Ibrahim; Salsabila Nova Calista; Falsyawal Galang Smarandreetha; Axlinabila Annisa Annasai (Prodi Sastra Inggris, Universitas Muhammadiyah Semarang, 2025)
This paper investigates how the body is objectified in Samiya At’ut’s flash fiction entitled That Summer Holiday. The story tells about the painful transition from childhood to adulthood especially in women. This idea is mostly being supported by McKinley and Hyde’s research in Objectified Body Consciousness Scale (OBCS). It is said that the objectifying of the body includes surveillance, body shame, and appearance control beliefs. Through qualitative method and explorative approach, the analysis of this paper includes how the girl has to face her body being objectified by her parents and surroundings. Living in religious circumstances, she is dictated on how to wear anything for her everyday life. In conclusion, it is clear that At’ut’s story underlines matters of how body is not belong to someone autonomously since it is always socially constructed.